Southward-Directed Subduction of the Farallon–Aluk Spreading Ridge and Its Impact on Subduction Mechanics and Andean Arc Magmatism: Insights From Geochemical and Seismic Tomographic Data - Iannelli, Sofía B.; Fernández Paz, Lucía; Litvak, Vanesa D.; Gianni, Guido; Fennell, Lucas M.; González, Javiera; Lucassen, Friedrich; Kasemann, Simone; Oliveros, Verónica; Folguera, Andrés (Frontiers in Earth Science, 2020)
Since the initial proposal of the past existence of a southward-directed mid-ocean ridge-subduction interaction in the Andes during Late Cretaceous-Paleogene times, several studies have been devoted to uncover the tectonomagmatic evidence of this process. The collision of a spreading ridge against a subduction margin provoke important tectonomagmatic changes; including between them variations in arc-related magmatic activity and in the plate-margin stress regime. However, the cryptic nature of the geological record often hampers assessing the influence and along-strike evolution of this process. In this study, we integrate new isotopic data with previous field and geochemical data on Andean arc-related magmatism, together with seismic tomography to track the main tectonic changes that affected the Andes between 35° and 42ºS from Latest Cretaceous to early Miocene times. In particular, we carry out a new tomotectonic analysis combining the regional bedrock record of the Late Cretaceous-early Miocene arc with upper-lower mantle seismic tomography. This analysis allowed us to unravel the main geodynamic changes that affected the Andean active-margin when the Farallon-Aluk spreading ridge was subducting. Besides, new isotopic analyses reveal the variable nature of the mantle source that fed the Late Cretaceous-early Miocene arc. Hence, the integration of geological, geochemical and geophysical data, together with new isotopic data studying the geochemical composition of the main Andean arc-related magmatic units in three main periods: 1) Latest Cretaceous-early Paleocene; 2) Early Paleocene-late Eocene; 3) Late Eocene-early Miocene, allow us to understand with an unprecedented detail the geochemical and spatio-temporal evolution of the passage of this spreading ridge along the Andean margin